Dynamics of Hindu Ceremonial Waste and Ecological Challenges: An Eco-Theological Cultural Analysis - Kadek Sugara Dana; I Gede Suwindia; I Nyoman Miarta Putra (LifeSciFi, 2026)
The issue of waste generated from Hindu religious ceremonies is escalating and poses potential ecological risks to the environment. Ritual activities involving items such as canang sari, banten (offerings), and other ceremonial paraphernalia generate both organic and inorganic waste, yet current management practices remain traditional. This study aims to describe the dynamics of ceremonial waste management, analyze the roles of the customary community and religious leaders, and examine the resulting ecological implications. A qualitative approach utilizing descriptive methods was employed. Data were gathered through in-depth interviews, observations, and documentation involving village officials, customary leaders, Hindu religious figures, PHDI administrators, and the residents of Rangdu Village. The findings indicate that ceremonial waste is still perceived as possessing sacred value. Consequently, management practices have not fully taken ecological aspects into account. Furthermore, the use of inorganic materials such as plastic in rituals exacerbates the environmental impact. Religious leaders and the customary community play a crucial role in fostering ecological awareness grounded in Tri Hita Karana values. The study concludes that a cultural eco-theological approach is essential to establish ceremonial waste management practices that are sustainable and aligned with the religious values ​​of the Balinese Hindu community.